The Determinants Of Audit Fees For Smes In Malaysia And Implications Of Mia Guidelines - Kasim, Mohd Nizam (2005)

(untitled)
To date, there has been little work done on developing countries especially issues on auditor independence, audit quality, audit delays, and audit fee determinants.